Histopathological spectrum of premalignant and malignant endometrial lesions. - Farhat Abbas; Farzana manzoor; Rahat Abas; Summyia Farooq; sabiha ashraf; Muzamil Latief (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: The incidence of premalignant and malignant endometrial disorders increases during the postmenopausal period and these disorders are one of the common gynecological malignancies. Early diagnosis of endometrial cancers with aggressive behavior and usually in pre-malignant stages may allow simpler treatment options and also decrease the treatment-associated morbidity risk.Objectives: To study histopathology premalignant and malignant endometrial lesions.Materials and methodsIt was a retro-prospective study that included 80 cases of endometrial hyperplasia and endometrial malignancies. The study was carried out from January 2018 to December 2019. The specimens were received as endometrial curettage, endometrial biopsy, and hysterectomy specimens. All specimens were fixed in 10% formalin. After a detailed gross examination, paraffin blocks of tissue were made; sections were cut and stained with hematoxylin and eosin. The sections were then studied under a microscope to categorize them into premalignant and malignant lesions.Results: Most patients were in the postmenopausal women age group of 41-60 were affected. Benign endometrial hyperplasia was seen in38(47.5%) atypical hyperplasia 14(17.50%), endometroid adenocarcinoma 23(28.75%), MMMT3(3.75%), endometrial stromal sarcoma in2(2.5%)s.Conclusion: The present study showed that endometrioid adenocarcinomas are the most common malignancies of the endometrium and are more common in postmenopausal women.